Currículos de matemática no ensino médio: em busca de critérios para escolha e organização de conteúdos - Silva, Marcio Antonio da (2009)
This work focus on the Mathematics Curricula for the Brazilian Ensino Médio, analyzing the criteria used in order to select and organize contents, once official orientations, as well as much of the research already carried out in our country, do not focus explicitly on what the guiding fundaments for selecting mathematic themes would be. The research is methodologically characterized as a theoretical essay, once we aim, using the argumentation, through the theoretical support, at the idea that it is necessary to search for criteria to select and organize mathematical contents to Ensino Médio, and they should take into consideration cultural features and the objectives of each community in order to fulfill the objectives of a school that aims equality through social transformation and, at the same time, valuing scientific knowledge built through many civilizations throughout the history of Humankind. In order to accomplish that, we look at Philosophy of Mathematics so we can understand how certain tendencies and conceptions about some concepts and the Mathematics itself can be explained; we think about William Doll Jr s work and his curricular criteria in a post-modern perspective; we use the concept of Critical Mathematical Education, following Skovsmose and we analyze the social and cultural factors of a curriculum. As far as the work organization is concerned, we emphasize the importance of breaking with the linear paradigm, which is still present in the Mathematics curricula, building a disposition based on net ideas. We resume our ideas through eight propositions concerning what the criteria to select and organize a critical and post-modern curricula would be: richness, recursion, relations, rigor, reflection, reality, responsibility and resignification. Finally, throughout our studies, we have concluded that Mathematics Curricula for Ensino Médio must present this science in its main plenitude, with all its research areas, reflecting that the inefficiency of certain contents in real situations do not make them less important, which is different from what has been currently done, as far as we are concerned, once Mathematics is divided and presented in an incomplete way. This creates an opportunity only for students who will keep on their studies in Educação Superior to study Mathematics in its richness and interconnections